Myocardial function in fetuses with lower urinary tract obstruction: Is there a cardiac remodeling effect due to renal damage?. (3rd June 2019) - Graupner, Oliver; Enzensberger, Christian; Götte, Malena; Wolter, Aline; Müller, Vera; Kawecki, Andreea; Weber, Stefanie; Degenhardt, Jan; Herrmann, Johannes; Axt‐Fliedner, Roland
Abstract: Objectives: Cardiac remodeling due to renal dysfunction may have an impact on myocardial function (MF) of fetuses with lower urinary tract obstruction (LUTO). The aim was to identify possible differences in MF in LUTO fetuses compared with healthy controls and to look for interactions between urine biochemistry and MF indices. Methods: This is a cohort study consisting of 31 LUTO fetuses and 45 healthy controls. Subgroups were generated according to intrauterine therapy (group 1: LUTO after therapy, group 2: LUTO without therapy at the time of examination, and group 3: controls). MF indices were measured using pulsed wave tissue Doppler imaging and M‐mode. Furthermore, results of fetal urine biochemistry were gathered retrospectively. Results: Among other findings, right ventricular (RV) e'/a' ratio was lower in group 1 compared with group 3 ( p = .050). According to gestational age (GA) level‐dependent analysis, RV isovolumetric relaxation time was significantly longer in group 2 compared with group 1 and group 3 at GA level 1 (19 wk of gestation). A significant positive correlation between RV e'/a' ratio and β‐2‐microglobulin as well as α‐1‐microglobulin and potassium could be observed. Conclusion: We observed differences in MF and an association between ventricular filling pattern and renal protein secretion in LUTO fetuses. This can be interpreted as a sign of intrauterine cardiac remodeling. Abstract : What's already known about this topic? Information about the impact of LUTO on fetal cardiac function is rare. It is assumed that megacystis compresses the iliac arteries, which lead to increased afterload. In LUTO, the renin‐angiotensin system is activated, which may also contribute to intrauterine cardiac remodeling. What does this study add? We observed differences in myocardial function in LUTO fetuses compared with healthy controls. An association between ventricular filling pattern and renal protein secretion was found in LUTO.